Case Report: Death penalty versus indefinite imprisonment in Japan: a case note of two court judgments involving autism spectrum disorder and autistic traits - Kashiwagi, Hiroko; Hirabayashi, Naotsugu (Frontiers in Psychiatry, 2026)
The World Psychiatric Association condemns the sentencing to death and execution of individuals with mental illness or intellectual and developmental disabilities. However, in Japan, death sentences have been confirmed in individuals diagnosed with delusional disorders and autism spectrum disorder (ASD). We report two Japanese court cases in which medical professionals with ASD or autistic traits committed multiple homicides. Although ASD characteristics were acknowledged, one defendant received the death penalty while the other was sentenced to indefinite imprisonment. This case note aims to analyze how psychiatric evaluations and judicial reasoning distinguished between these two outcomes. We highlight the reliance on subjective assessments of remorse and the limited standardization in evaluating rehabilitation potential when distinguishing between the death penalty and indefinite imprisonment in defendants with ASD traits. Psychiatric expertise should contribute to fairer and more evidence-based sentencing.